Ablation of EWS-FLI1 by USP9X inhibition suppresses cancer cell growth in Ewing sarcoma. (1st January 2023) - Wang, Shan; Huo, Xiaofang; Yang, Yiping; Mo, Yingxi; Kollipara, Rahul K.; Kittler, Ralf
Abstract: The neomorphic transcription factor EWS-FLI1 is a key driver of Ewing sarcoma. Ablation of EWS-FLI1 may present a promising therapeutic strategy for this malignancy. Here we found that the deubiquitinase, ubiquitin specific peptidase 9 X-linked (USP9X) stabilizes EWS-FLI1 protein expression in Ewing sarcoma. We show that USP9X binds the ETS domain of EWS-FLI1 in Ewing sarcoma cells and deubiquitinates EWS-FLI1 and that USP9X and EWS-FLI1 protein expression is correlated in clinical Ewing sarcoma specimens. We found that treatment of Ewing sarcoma cells with the USP9X inhibitor WP1130 mediates rapid EWS-FLI1 degradation in vitro and in vivo which coincides with reduced growth of Ewing sarcoma cells and tumors. Our results suggest that USP9X might be a potential therapeutic target to mediate EWS-FLI1 depletion in Ewing sarcoma. Highlights: USP9X interacts with EWS-FLI1 through the ETS domain. USP9X deubiquitinates and stabilizes EWS-FLI1. USP9X inhibition by WP1130 could reduce cell proliferation of Ewing sarcoma. USP9X loss and inhibition affects migration of Ewing sarcoma cells.